Continuous-wave lasing of AlGaN-based ultraviolet laser diode at 274.8 nm by current injection. (1st April 2022) - Zhang, Ziyi; Kushimoto, Maki; Yoshikawa, Akira; Aoto, Koji; Schowalter, Leo J.; Sasaoka, Chiaki; Amano, Hiroshi
Abstract: We demonstrated continuous-wave lasing of an AlGaN-based ultraviolet laser diode, fabricated on a single-crystal AlN substrate when operating at 5 °C. The threshold current density and device series resistance were reduced by improvements to the epitaxial structure and electrode arrangement. A peak wavelength of 274.8 nm was observed for lasing at a drive current over 110 mA, which corresponded to a threshold current density of 3.7 kA cm −2 . The operating voltage at the threshold current was as low as 9.6 V.